Histological and histochemical aspect of the testicular cycle of a hill stream teleost, Botia almorhae (Day) - Pathani, S S; Joshi, S K (The Indian Journal of Animal Sciences, 2007)
Seasonal histological and histochemical changes are seen in the testes of the fish Chital, Botia almorhae, studied for 2 years (2000 and 2001) at Kumaun Himalaya A lobular like highly convoluted paired testes of the fish, showed a number of seminiferous lobules with lobular wall. It has germinal epithelium which varied according to the reproductive cycle. Histological structure of spermatogonia, spermatocytes, secondary spermatocytes, spermatidss and sperms of testis of Botia almorhae has been studied. The anterior and middle parts of the testis are functional and distal end is non- functional during testicular cycle. Seasonal cycle of fish shows resting phase (mid October to late January), early maturing (late January to February), advance maturing (March to mid April) and mature phases (mid April to August). The spent phase extended from mid August to October in the testis of the fish collected from lotic water (SuyalKosi rivers) of Kumaun Himalaya. Similarly, the histochemical changes in carbohydrates, proteins and lipids in the testicular cycle and gonadosomatic index (GSI) of Botia almorhae have been recorded in the paper for the first time.